Middle Square Method Analysis of Number Pseudorandom Process - Arif Budiman; Efori Bulolo; Imam Saputra (The IJICS (International Journal of Informatics and Computer Science), 2020)
Random numbers can be generated from a calculation of mathematical formulas. Such random numbers are often referred to as pseudo random numbers, random numbers are used for various algorithms, especially cryptographic algorithms such as AES, RSA, IDEA, GOST that require the use of Middle-Square Method random numbers which is very useful for adding research references to algorithms concerning random number generator and better understand how random numbers are generated using the Middle-Square Method algorithm. Both data collection and report making as for the objectives achieved in the form of understanding random numbers and knowing the algorithm process, compile a program designed to be used as an alternative to random numbers for various purposes, especially in cryptographic algorithms.